Pengaruh Kadar Perekat Molase dan Lama Pengeringan terhadap Proses Pembuatan Biobriket dari Tempurung Kelapa dan Sekam Padi - Andesta Celya Harlina; Ropiudin Ropiudin; Abdul Mukhlis Ritonga (Journal of Agricultural and Biosystem Engineering Research, 2021)
Biobriquette is an alternative fuel that is environmentally friendly because it uses organic materials. Wastes that can be used for biomass briquettes include agricultural wastes such as coconut shells and rice husks. Briquettes are also made using certain adhesives as a hardener in briquettes. The purpose of this study was to determine the effect of molasses adhesive content and drying time on the quality of biobriquette manufacture, with this study useful for reducing energy use to be used as fuel, reducing coconut shell and rice husk waste, and also knowing the molasses adhesive content and drying time required. appropriate for the manufacture of biobriquettes. In this study, there were 2 factorials, namely the amount of molasses adhesive content of 30%, 40%, 50% and drying time of 5 hours, 6 hours, 7 hours with a combination of both treatments. Testing the characteristics of biobriquettes includes the value of water content, ash content, volatile matter, density, and combustion rate. Parameters used as reference are in accordance with Indonesian briquette quality standards. From the results of the research, it is known that the molasses adhesive content and the appropriate drying time are K1W3 samples with an adhesive content of 30% and a drying time of 7 hours because of the lowest water content value and also produces good and durable briquettes when burning briquettes.